Methane emission under alternative irrigation regimes in Malaysian rice cultivation - Pauzai, Nur Fitriah; Sulaiman, Muhammad Firdaus; Mohd Amin, Adibah; Jamal Jaganathan, Nur Azleen; Mohd Hashim, Amalia; Md Suptian, Mohd Fairuz (Malaysian Society of Soil Science, 2023)
Rice cultivation under continuous flooding (CF) is a major anthropogenic emitter of methane gas (CH4) due to the oxygen-deprived state of the submerged soil. The potential of alternative irrigation regimes i.e., mid-season drainage (MD) and alternate wetting and drying (AWD) to reduce CH4 emissions from Malaysian rice cultivation was investigated in the present study. Rice (Oryza sativa var. MR297) was transplanted into 15 tanks and randomly assigned to each of the three treatments: CF, MD and AWD in a randomized complete block design (RCBD). Emissions of CH4 were measured weekly by collecting air samples using static chambers and analyzing the air samples for CH4 concentration using gas chromatography (GC). The present study found that cumulative CH4 emissions per planting cycle were 70.24, 30.75, and 15.93 g CH4 m−2 from treatments CF, AWD, and MD, respectively. Methane emissions of the MD and AWD treatments were 77.07 and 57.81 lower, respectively, compared to CH4 emissions of CF. The present study indicated that AWD and MD had the potential to reduce CH4 emissions in rice cultivation.